Threat Status of Saussurea lappa-a study in Bhaderwah area of Jammu & Kashmir India. - Singh, Mohan; Raina, Rakesh Kumar; Hassan, Wahid-ul-; Malik, Iftikhar Ahmad (International Research Journal of Ayurveda & Yoga, 2021)
Saussurea lappa being one of the most sought-after species in the pharmaceutical industry, providing good dividends to the States//UTs from where it is procured, is rapidly declining in nature. The threat perception of the species changes every single day. This highly beneficial herb, is under immense pressure to survive in natural habitat. The threat status of Saussurea lappa has increased manifold from last 15 years. The present study entitled as “Threat status of Saussurea lappa -a study in Bhaderwah area of Jammu & Kashmir India, was conducted at Bhaderwah, District Doda a High-Altitude area where the species has a natural agro-climatic condition to thrive. A comprehensive protocol was framed. From this study it was concluded that Illegal/Unsustainable extraction from the Forests is a major cause for dwindling species of Saussurea lappa. Lack of understanding of sustainable harvesting/extraction has led to disturbance of habitat, loss of diversity, reduced abundance and local declining of Saussurea lappa.